THE CITY AS AN EXHIBITION: CINEMATIC, THEATRICAL, AND MUSEUM APPROACHES TO THE ORGANIZATION OF SPACE - Troshkina, Olena (Theory and practice of design, 2025)
The article explores the concept of museum exhibitions applied to the urban environment, where architectural objects and spaces function as elements of a visual exposition. The purpose of the study is to identify the potential of cinematographic, theatrical, and exhibition-based approaches in the formation and perception of urban space. The architectural environment is interpreted as an exposition operating according to the principles of a stage, film frame, and exhibition space. The methodological basis is an interdisciplinary analysis that combines principles of cinematography (frame sequence, gaze movement), theatre (mise-en-scène, scenography), and museum studies (exhibition space, scenario, visual accents). Comparative, typological, and semantic approaches to the urban environment are applied. Results. The study substantiates the relevance of perceiving the city as an exposition with its own route, dramaturgy, and compositional nodes. Architectural objects are interpreted as “exhibits”, while spatial transitions are understood as sequences of frames or scenes. Analogies are identified between museum techniques (centering, isolation, lighting, spatial dilution) and urban planning tools (dominant elements, perspective axes, squares, cour d’honneur, light accents). The role of scenario-based perception and sequential spatial experience in shaping environmental dramaturgy is confirmed. Scientific novelty. For the first time, the city is proposed as an exposition system with a scenario-based logic grounded in the principles of cinema, theatre, and the museum. The study substantiates the relevance of analyzing urban space as a narrative structure, in which meanings are formed through the organization of routes, spatial accents, and human interaction. Practical relevance. The results can be applied in urban planning, urban design, and the renovation of urban areas. The approach enhances spatial legibility, emotional engagement, and the formation of environmental identity. Scenario-based and exhibition-oriented strategies reinforce the city’s role as a communicative and cultural system.